MENGOPTIMALKAN PENGUASAAN AKSARA JAWA KELAS X DI SMA MELALUI BLENDED LEARNING - Yunitasari, Mela (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2024)
ABSTRACT This research aims to optimize the mastery of Javanese script for Class X at SMA Labschool UNESA through the implementation of the Blended Learning model as an innovative strategy in Javanese language learning. Javanese script is an important aspect of cultural preservation and local identity, but students' mastery of this script tends to be low due to the use of conventional and less engaging teaching methods. The classroom action research is conducted in two cycles, with each cycle including planning, implementation, observation, and reflection. The subjects of the research are the Class X students of SMA LABSCHOOL UNESA 1. Data collection techniques include observation, tests, interviews, and documentation. The Blended Learning model applied combines face-to-face learning with online learning methods through interactive digital media, such as online quizzes, educational videos, and character practice using educational applications. The results of this study indicate a significant improvement in the mastery of Javanese Script among students from cycle I to cycle II, both in terms of reading and writing skills. Moreover, the enthusiasm and participation of students in the learning process also showed a remarkable increase. Thus, Blended Learning is effective in enhancing students' abilities to master Javanese Script and building motivation and positive attitudes towards the preservation of local culture. This study recommends the sustainable implementation of a similar model for Javanese language learning that is more relevant and contextual with the times. ABSTRAK Penelitian ini memiliki tujuan untuk mengoptimalkan penguasaan Aksara Jawa kelas X di SMA Labschool UNESA melalui penerapan model pembelajaran Blended Learning sebagai strategi inovatif pada pembelajaran Bahasa Jawa. Aksara Jawa ialah salah satu aspek penting dalam pelestarian budaya dan identitas lokal, namun penguasaan peserta didik terhadap aksara ini cenderung rendah karena penggunaan metode pembelajaran yang dipergunakan masih bersifat konvensional dan kurang menarik. Penelitian tindakan kelas dilaksanakan dalam dua siklus, dengan setiap siklus mencakup perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas X SMA LABSCHOOL UNESA 1. Teknik pengumpulan data meliputi observasi, tes, wawancara, dan dokumentasi. Model Blended Learning yang diterapkan menggabungkan pembelajaran tatap muka dengan menggunakan metode pembelajaran daring melalui media interaktif berbasis digital, seperti kuis daring, video pembelajaran, serta latihan aksara menggunakan aplikasi edukatif. Hasil penelitian pada penelitian ini menunjukkan ada peningkatan signifikan dalam penguasaan Aksara Jawa peserta didik dari siklus I ke siklus II, baik dari segi kemampuan membaca ataupun menulis Aksara Jawa. Selain itu, antusiasme dan partisipasi siswa dalam proses pembelajaran juga mengalami peningkatan yang mencolok. Dengan demikian, Blended Learning efektif dalam meningkatkan kemampuan siswa dalam menguasai Aksara Jawa serta membangun motivasi dan sikap positif terhadap pelestarian budaya lokal. Penelitian ini merekomendasikan penerapan model serupa secara berkelanjutan untuk pembelajaran Bahasa Jawa yang lebih relevan dan kontekstual dengan perkembangan zaman.